THE LIFE, ISLAMIC HISTORIOGRAPHY AND ENVISAGEMENT OF HZ. MUHAMMAD OF ABDULHAMİD GÖLPINARLI - Zekeriya AKMAN (Fırat University, 2019)
Abdülbaki Gölpınarlı was born on January 12, 1900 in İstanbul. He is a scholar who hails from caucasian origin. He was graduated from Istanbul University, Faculty of Literature. He lectured on a History of Literature and Suphism at University. He passed away in Istanbul in 1982. Literary historian, scholar, poet, and the Gölpınarlı, Mevlevi Order known as an expert in research. Abdülbaki Gölpınarlı, as a versatile scholar, carried out studies on Literature, History of Literature, History of Suphism and wrote many books and articles. Made translations from Arabic and Persian. Abdülbaki Gölpınarlı, Literature and History of Islam and the Prophet, as well as work in the field of Sufism. Wrote works about the life of Muhammad. As the branch itself, although the Islamic historian and worked in this area. In the studies related to History of İslam, he introduced Hz. Muhammad, Hz. Ali, Twelve Imams and Hz. Fatıma. Studies on the History of the Prophet of Islam has made. Ali and Ahl-ul-Bayt concentrated more focused way. In the books of courses of religion which were written for students he explained Islam, life and personality of Hz. Muhammad in his own style. Abdülbaki Gölpınarlı had different approaches to Hz. Muhammad and Ehli Beyt and made some original comments about some events. Works were written on the Prophet studied as a textbook in schools. He gave prominence to humane specialities of Hz. Muhammed, such as morality, industriousness, where narrating his life. Books Hz. Muhammad accuracy, precision, diligence, cleanliness and superior qualities such as kindness to the fore increased the.